Legal and Public Health Governance for Sustainable Integration of Mobile Health (mHealth) Technologies in East Africa - Paul Atagamen Aidonojie; George Mulingi Mugabe; Esther Chetachukwu Aidonojie; Muwaffig Jufri; Mundu M. Mustafa; Collins Ekpenisi; Obieshi Eregbuonye; Godswill Owoche Antai; Mercy Okpoko; Uzoho Kelechi; Khalid Saleh Y Alammari (Buletin Ilmiah Sarjana Teknik Elektro, 2026)
Mobile health (mHealth), which comprises mobile health applications, telemedicine, SMS-based treatments, and wearable health monitors, has the power to change healthcare delivery, but at the same-time, it is going through a rapid developmental phase that regulators cannot keep up with. This is considered a necessity in balancing the Integration of mHealth technology innovation through enhanced laws within East Africa. It is in view of this that this examines the legal and public health framework in integrating mHealth technology in enhancing the healthcare system within East Africa. The study adopts a doctrinal and systematic analytical method of study directed by the PRISMA framework, allowing thorough legal analysis while at the same time guaranteeing a transparent, stringent, and comprehensive review of related literature. The study found that fragmentation of laws, lack of centralized public health and data governance, unequal access to mHealth services, and constraints on innovation, weakens the integration and regulation of mHealth. Hence, the study recommends and concludes that for effective integration of mHealth in enhancing the public health care system, the research insists on a unified legal system that states unambiguously which data protection benchmarks apply, what the liability conditions are, what the integration of different systems and regulations requirements is, and how to coordinate among different countries' regulators. Besides that, it suggests measures for strengthening the capacity of the targeted groups, such as: medical professionals, trainees, users’ digital literacy campaigns, and local mHealth technology developers’ institutions’ support.